Economic nationalism and decolonization: West Africa in comparative perspective - Olukoju, Ayodeji (Hagar: Studies in Society and Culture, 2010)
This paper analyzes the phenomenon of economic nationalism as part of the decolonization process in West Africa, especially from the 1930s to the 1950s. It examines the economic thought, policies and practice of both non-state actors (African entrepreneurs and other nationalists) and state actors (the emergent nationalist governments of Ghana and Nigeria during the 1950s). Economic grievances against the colonial state and expatriate firms drove much of the nationalist activities in West Africa during this period. These ranged from unfair allocation of scarce shipping space during World War I to the near exclusion of African exporters and importers by external trade control schemes during World War II. Groups of indigenous private entrepreneurs formed "political enterprises" (trade and banking corporations) in the inter-war period, while self-governing administrations of African nationalists during the 1950s established shipping lines to break the stranglehold of expatriate shipping conferences. The paper concludes by setting the discussion in the comparative context of anti-foreign economic nationalism in the Middle East and other regions of Asia during the nineteenth and twentieth centuries. This makes for a better appreciation of the peculiarities of the processes of decolonization and independence in West Africa.